A compliation of seafdec AQD technical papers on milkfish & other finfishes (Philippines, 1983)
This book provides technique to induce maturation and spawning in wild and captive adult milkfish, the development of the technique for the mass production of milkfish fry,...
Keywords: Nuôi trồng thủy sản,Aquaculture,Fisheries